Audit Risk Management pada Sistem Evaluasi dan Pengawasan Realisasi Anggaran di Kabupaten Gianyar Menggunakan Kerangka Kerja COBIT 2019 dan NIST 800-30 - Oka Semara Putra, I Made; Linawati, Linawati; Setiawan, I Nyoman (Majalah Ilmiah Teknologi Elektro; Vol 22 No 2 (2023): (Juli - Desember) Majalah Ilmiah Teknologi Elektro, 2024)
The Development Administration Section is an organization in the field of government in Gianyar Regency which has a work program which is to supervise the realization of the budget for each RAO (Regional Apparatus Organization) and is assisted by using the TEPRA Information System to carrying out a routine evaluation process every month, so it is important for the information system to minimize the risks that may occur. The research process uses two frameworks, namely the COBIT 2019 framework and the NIST 800-30 framework. The use of NIST 800-30 found 12 gaps out of 12 threats with 8 risks being medium and 4 risks being low. Continuing the use of COBIT 2019 resulted in calculating the highest rating value in the first process APO 13 domain with a value of 4.58, a percentage of 91%, Fully category. And the domain with the lowest percentage with a value of 3.00, the percentage is 60%, the Largely category is the second and third process APO 13 domain, DSS 02 domain, first and second process DSS 03 domain and DSS 04 domain. Next, the assessment of maturity levels produces the highest score in BAI 05 domain with a value of 4.27, level value 4 (Quantitative). And the domain with the lowest score with a value of 3.00, the level value 3 (Defined) occurs in the domain DSS 02, DSS03, and DSS 04. Next, the gap level assessment with the highest value occurs in the third process APO 14 domain with a value of 1.92 which is the level of effectiveness in using problem data that does not run smoothly according to system functionality. Based on the results of the research conducted, it is hoped that it will create a developing government and create good governance, so that in the process of developing an information system, the recommendations for improvements that have been suggested can be implemented.